2016
DOI: 10.1002/2015gl066818
|View full text |Cite
|
Sign up to set email alerts
|

Segmented Hellenic slab rollback driving Aegean deformation and seismicity

Abstract: The NE dipping slab of the Hellenic subduction is imaged in unprecedented detail using teleseismic receiver function analysis on a dense 2‐D seismic array. Mapping of slab geometry for over 300 km along strike and down to 100 km depth reveals a segmentation into dipping panels by along‐dip faults. Resolved intermediate‐depth seismicity commonly attributed to dehydration embrittlement is shown to be clustered along these faults. Large earthquakes occurrence within the upper and lower plate and at the interplate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 50 publications
6
54
0
2
Order By: Relevance
“…These segments are delimited by vertical offsets of up to 10 km and are believed to be bounded by transform faults inherited from a spreading ridge. The profiles of Sachpazi et al (2016) also showed a bend in the slab at 60 km depth, which is consistent with the geometry of the Wadati-Benioff Zone (WBZ) beneath the region (Hatzfeld, 1994;Papazachos et al, 2000).…”
Section: 1002/2017jb015154supporting
confidence: 74%
See 4 more Smart Citations
“…These segments are delimited by vertical offsets of up to 10 km and are believed to be bounded by transform faults inherited from a spreading ridge. The profiles of Sachpazi et al (2016) also showed a bend in the slab at 60 km depth, which is consistent with the geometry of the Wadati-Benioff Zone (WBZ) beneath the region (Hatzfeld, 1994;Papazachos et al, 2000).…”
Section: 1002/2017jb015154supporting
confidence: 74%
“…Compared to the previous images of Pearce et al (), the only change is an upward shift of the slab structure by up to 3 km. From the tomographic models, the GRT‐RF images, and from the 3‐D receiver function study of Sachpazi et al (), we picked both the subducting Moho and the slab top (where possible). In Figure , we show that the new estimate of the subducting Moho fits these studies within approximately 5 km (vertically).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations